Status, opportunities, and future of smart personal protection equipment in construction site: Patent analysis - Xiaoxiang, Qin; Junjia, Yin; Alias, Aidi Hizami; Haron, Nuzul Azam; Hua, Law Teik (International Journal of Innovative Research and Scientific Studies, 2025)
Personal protective equipment (PPE) plays a vital role in ensuring workers’ safety on construction sites. This study aims to analyze the current state, opportunities, and future trends of PPE through a systematic patent analysis, providing insights into its technological advancements and development strategies. A comprehensive patent analysis was conducted by searching and evaluating relevant databases to categorize the main types of PPE used in construction, including helmets, protective eyewear, safety shoes, and safety belts. The study assessed the technological level and innovation of each type of equipment. Furthermore, emerging opportunities in PPE development, such as smart wearable devices, the application of IoT technology, and advancements in material science, were explored to align with market demand and technological trends. The results indicate that PPE in construction is evolving towards enhanced intelligence, connectivity, and performance efficiency. Innovations in smart wearables and IoT integration are improving real-time monitoring and adaptive safety measures. Additionally, material research is driving advancements in durability and user comfort. These developments collectively contribute to a more comprehensive safety framework for construction workers. With continuous technological progress and increasing safety awareness, PPE in construction is expected to achieve significant breakthroughs in intelligence and humanization. Future strategies should focus on improving comfort, adaptability, and comprehensive protection to enhance worker safety. This study provides theoretical support for PPE development and practical references for industry stakeholders, including manufacturers, policymakers, and construction firms. The findings offer guidance on optimizing PPE design and functionality to align with evolving safety needs in construction environments.